EFFECT OF RAW ALAY MUMMY (SHILAJIT) ON BLOOD COAGULATION PARAMETERS IN DOGS - Kurbanova Diloramxon Ibragimdjon qizi (Western European Studies, 2025)
This study investigated the effect of raw Alay mummy (Shilajit) on several blood coagulation parameters in dogs. The substance was administered orally at a dose of 50 mg/kg, and blood samples were analyzed before and 30 and 60 minutes after administration. Significant prolongation of clotting time, plasma recalcification time, and thrombin time was observed (P < 0.01), along with increased plasma tolerance to heparin and fibrinolytic activity. A slight decrease in fibrin concentration and moderate rise in P-, U-, and UP ± X-factors were also noted. These findings indicate that Alay mummy exerts anticoagulant and fibrinolytic effects, likely through activation of endogenous anticoagulant mechanisms and enhancement of fibrin degradation. The results suggest potential use of Alay mummy as a natural regulator of blood coagulation and in the prevention of thrombotic conditions
Keywords: Alay mummy; Shilajit; blood coagulation; fibrinolysis